2006
DOI: 10.1529/biophysj.105.077453
|View full text |Cite
|
Sign up to set email alerts
|

Catch Force Links and the Low to High Force Transition of Myosin

Abstract: Catch is characterized by maintenance of force with very low energy utilization in some invertebrate muscles. Catch is regulated by phosphorylation of the mini-titin, twitchin, and a catch component of force exists at all [Ca2+] except those resulting in maximum force. The mechanism responsible for catch force was characterized by determining how the effects of agents that inhibit the low to high force transition of the myosin cross-bridge (inorganic phosphate, butanedione monoxime, trifluoperazine, and blebbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 38 publications
3
43
2
Order By: Relevance
“…Since twitchin is a thick filament protein, this would bind the two filaments and provide the necessary rigidity, and the phosphorylation dependence of the interaction explains how catch is controlled. However, this still left a nagging problem: although the actomyosin crossbridges were not the stress resistant structure in the catch state, various lines of evidence showed that when myosin is generating force catch force decreases, and when it is not, catch force increases, suggesting that the twitchin linkages and actomyosin force generating crossbridges interact in some way (Butler et al, 2006).…”
Section: Post-1997-mentioning
confidence: 99%
See 1 more Smart Citation
“…Since twitchin is a thick filament protein, this would bind the two filaments and provide the necessary rigidity, and the phosphorylation dependence of the interaction explains how catch is controlled. However, this still left a nagging problem: although the actomyosin crossbridges were not the stress resistant structure in the catch state, various lines of evidence showed that when myosin is generating force catch force decreases, and when it is not, catch force increases, suggesting that the twitchin linkages and actomyosin force generating crossbridges interact in some way (Butler et al, 2006).…”
Section: Post-1997-mentioning
confidence: 99%
“…Thick filament is bottom thick line, the myosin head is the object resembling a microphone, the thin filament is the row of open circles, and twitchin is the object represented as a coil (unphosphorylated and unable to interact with the thin filament) and straight lines (interacting with the thin filament in alteration with myosin in ACh and continuously during catch in saline). Modified from Funabara et al (2005) and Butler et al (2006).…”
Section: Abbreviation Listmentioning
confidence: 99%
“…Determination of IGDXD1IG and DXD1 binding to thin filaments was done using a modification of the co-sedimentation technique described by Shaffer et al (32) for measuring binding of various fragments of myosin-binding protein C to F-actin. The assay solution was based on a relaxing solution used for permeabilized muscles (24,25). It contained 30 mM PIPES, 20 mM EGTA, 3 mM MgATP, 3 mM free Mg 2ϩ , 1 mM DTT, and 21 mM 1,6-diaminohexane-N,N,NЈ,NЈ-tetraacetic acid (HDTA), pH 6.8.…”
Section: Peptide Synthesis and Recombinant Protein Expression Andmentioning
confidence: 99%
“…Mechanical Measurements on Permeabilized ABRM-Muscles were dissected, permeabilized with Triton X-100, and subjected to mechanical measurements as described previously (24). The relaxing solution contained 3 mM MgATP, 5 mM phosphocreatine, 20 mM EGTA, 3 mM free Mg 2ϩ , 1 mM DTT, 30 mM PIPES, 15.6 mM HDTA, 1 mg/ml creatine phosphokinase, 0.5 mM leupeptin, pH 6.8.…”
Section: Peptide Synthesis and Recombinant Protein Expression Andmentioning
confidence: 99%
See 1 more Smart Citation